Color-changing fluorescent DNA probe containing solvatochromic Dansyl-nucleoside surrogate for sensing local variation of DNA duplex. (1st March 2022) - Cui, Haonan; Fang, Jiaobing; Sun, Minglei; Liu, Ziqi; Li, Zijin; Liu, Kaifu; Liu, Mingzhe
Graphical abstract: Abstract: A novel Dansyl-nucleoside surrogate (Dns ) based on (±)- trans -4-(hydroxymethyl) piperidin-3-ol was designed and synthesized. The Dns exhibited excellent solvatochromic properties. About 90 nm of red-shift accompanied color change from green to orange could be achieved with an increase of solvent polarity. The Dns was incorporated into oligodeoxynucleotide by phosphoroamidite chemistry. Two kinds of Dns -incorporated fluorescent DNA probes were designed and synthesized for sensing variation of DNA duplexes based on color-changing manner. As a result, the color-changing DNA probe not only can detect complementary oligonucleotide, but also can distinguish mismatch flanked in Dansyl/nucleobase pair by naked eye. Moreover, the change of fluorescence color of sample solutions could be captured by smartphone, and the photographs could be digitalized by image-processing software. Thus, the Dns -incorporated fluorescent DNA probe is expected to open the way to point-of-care assays in the future.